Collective Identity Development Amid Institutional Chaos: Boundary Evolution in a Women's Rights Movement in Post Gaddafi Libya. Issue 10 (October 2022) - Basir, Nada; Ruebottom, Trish; Auster, Ellen
Collective identity is important for the cohesion of social movements, yet there is an inherent tension between group unity and heterogeneity when multiple groups are motivated to come together to work for change. Through a three-year investigation of the early stages of a women's rights movement following the Libyan revolution, we explore the dynamics of collective identity development. Our findings capture how two heterogeneous groups, Libyan locals and Libyan diaspora, interact to negotiate and re-negotiate the boundaries of collective identity. We find that this process unfolds through an ongoing struggle where the point of difference between the groups—their uncommon past —is the mechanism first used to ensure inclusion of insiders, and then to exclude outsiders from the collective identity. Our paper contributes to our understanding of the relational process through which collective identity co-evolves, and the challenges faced by heterogeneous groups engaging in collective action.